THE ROLE OF BRONCHOSCOPY IN INTENSIVE CARE MEDICINE, CASE REPORT - Atanas Zanev (Peytchinski Publishing, 2024)
Purpose. Airway maintenance, adequate ventilation, and pulmonary gas exchange are crucial for critically ill patients. The challenges of performing in intensive care patients often differ significantly from routine surgical procedures in the operating room. The aim of our study was to assess the effectiveness of bronchoscopic aspiration in improving respiratory function in a patient on prolonged artificial ventilation. Material/Methods. A 69-year-old male was admitted to the ICU six days after an open cystoprostatectomy, presenting with respiratory failure. Initial treatment included blind airway suctioning, nebulization, chest physiotherapy, and empirical antibiotics. Due to persistent atelectasis and respiratory failure, bronchoscopic aspiration was performed. A total of nine bronchoscopies with bronchoalveolar lavage (BAL) were conducted for aspiration and microbiological testing, guiding adjustments in antibiotic therapy. After 61 days in the ICU, the patient was transferred to the Department of Urology and later discharged. Results. Bronchoscopic aspiration significantly improved the patient's condition, with noticeable improvements after the first bronchoalveolar lavage (BAL). Pulmonary imaging on X-ray and blood oxygenation showed clear progress, with better lung function and enhanced ventilation parameters. These changes allowed for a reduction in oxygen concentration and improved gas exchange. After 61 days in the ICU, the patient was successfully transferred to the Department of Urology and later discharged in stable condition. Conclusions. Bronchoscopic aspiration is a highly effective method for improving ventilation and oxygenation in patients on prolonged mechanical ventilation. It plays a crucial role in managing airway obstructions atelectasis, and enhancing microbiological diagnostics.